One-year changes in physical performance in world-class team handball players from Danish national youth teams - Jensen, K.; Johansen, L.; Liwendahl, F. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The physical part of a team handball game consists of a combination of intense, intermittent activities such as running, sprinting, jumping as well as regular infights between players - holding and pushing. Physical demands in international handball can be evaluated by measuring physical performance of the best players. Describing changes in successful young players indicate which physical factors are the most important to develop. No difference was seen in Body fat, VO2max, Blmax, HRmax, T5m, T30m, CMJ, SST, S3S or SJU (P>0.05), while body weight and fat free mass increased by 1.6 and 2.0 kg or 1.9 and 2.9%, respectively (P<0.01). Tmax, and 30mshuttle increased 22 sec and 354 m or 4.9 and 8.6%, respectively (P<0.05). CMJ½BW increased by 1.4 cm or 9.9% (P<0.001). 1RM increased by 8, 14 and 7 kg or 11, 14 and 9% in power clean, squat and bench press, respectively (P<0.001). Accordingly, after one year of training the players increase body weight and fat free mass and variables related to strength such as CMJ½BW and 1RM in strength exercises. Time to exhaustion in maximal treadmill run and distance covered during shuttle run also increase. However, no changes are seen in functional exercises as 30 m sprint and different shots. Aerobic work capacity per kg body weight is maintained although body weight increases. It is concluded that successful players competing at international level in team handball is depending more on changes in variables alluding to strength properties rather than on variables related to aerobic capacity.